Rural end-of-life care from the experiences and perspectives of patients and family caregivers: A systematic literature review. (December 2017) - Rainsford, Suzanne; MacLeod, Roderick D; Glasgow, Nicholas J; Phillips, Christine B; Wiles, Robert B; Wilson, Donna M
Background: End-of-life care must be relevant to the dying person and their family caregiver regardless of where they live. Rural areas are distinct and need special consideration. Gaining end-of-life care experiences and perspectives of rural patients and their family caregivers is needed to ensure optimal rural care. Aims: To describe end-of-life care experiences and perspectives of rural patients and their family caregivers, to identify facilitators and barriers to receiving end-of-life care in rural/remote settings and to describe the influence of rural place and culture on end-of-life care experiences. Design: A systematic literature review utilising the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data sources: Four databases (PubMed, CINAHL, Scopus and Web of Science) were searched in January 2016, using a date filter of January 2006 through January 2016; handsearching of included article references and six relevant journals; one author contacted; pre-defined search terms and inclusion criteria; and quality assessment by at least two authors. Results: A total of 27 articles (22 rural/remote studies) from developed and developing countries were included, reporting rural end-of-life care experiences and perspectives of patients and family caregivers. Greatest needs were informational (developed countries) and medications (developing countries). Influence of rural location included distances, inaccessibility to end-of-life care services, strong community support and importance of home and 'country'. Conclusion: Articulation of the rural voice is increasing; however, there still remain limited published rural studies reporting on patient and family caregivers' experiences and perspectives on rural end-of-life care. Further research is encouraged, especially through national and international collaborative work.